Water Sustainability Initiatives to Meet the Water Crisis in India - Jena, Madhab C.; Mishra, Sarat K.; Moharana, Himanshu S. (Journal of Chemical Engineering Research Updates, 2023)
One of the most pressing global challenges we face today is the rapid growth of the population. As the population continues to expand, the need for rapid industrialization has become paramount. However, this industrialization and urbanization have given rise to a significant and detrimental consequence: environmental pollution. This pollution, in turn, has led to various crises, including those related to water, food, and air quality. Water, being an essential element for human existence, is of utmost importance. Without access to clean and sufficient water, life on Earth would be unsustainable. Unfortunately, India has been grappling with a prominent water crisis, particularly during the summer seasons, resulting in the loss of countless lives each year. Even during other seasons, the availability of water is often satisfactory, but the quality of water remains a concern in many parts of the country. The shortage of water can be attributed primarily to the declining levels of underground water and the ever-increasing demand for this precious resource. India receives ample rainfall during the monsoon season; however, a significant portion of this water flows into the oceans, causing floods in various regions. Conversely, during the summer months, the scarcity of water leads to droughts in many areas. Therefore, it is imperative to initiate sustainable water management practices, including rainwater harvesting, to address this water crisis. This review article delves into various types of water sustainability initiatives with a structured approach and analyzes the associated challenges. Additionally, it proposes detailed systems that can be implemented to enhance water availability and distribution throughout the country. These measures are crucial steps toward mitigating the water crisis and ensuring a sustainable water future for India.